2018
DOI: 10.12659/msm.910740
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Regulates Inflammatory Response and Oxidative Stress via Nuclear Factor kappa B (NF-κB) and NF-E2-Related Factor 2 (Nrf2) Signaling Pathways in Ankle Fractures in Children

Abstract: BackgrounThis study aimed to investigate the effects of SIN on ankle fracture and the underlying mechanisms in MG-63 cells.Mateeial/MethodsqRT-PCR and ELISA assay were used to detect the mRNA and protein levels of cytokines in peripheral blood of children with or without ankle fracture. The expression and activity of antioxidant and detoxifying enzymes were detected by ELISA assay. Pretreated MG-63 cells with/without SIN were stimulated with 1 μg/ml bradykinin (BK). A CCK-8 kit was used to detect the cell viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The production of inflammatory cytokines is related to oxidative stress, and promotes osteoclastogenesis and bone resorption [ 37 , 38 , 39 , 40 ]. Moreover, several articles reported that LPS and IFN-γ are a crucial cytokine for the inflammation process via the activation of proinflammatory mediators such as NO, iNOS, and COX-2 [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The production of inflammatory cytokines is related to oxidative stress, and promotes osteoclastogenesis and bone resorption [ 37 , 38 , 39 , 40 ]. Moreover, several articles reported that LPS and IFN-γ are a crucial cytokine for the inflammation process via the activation of proinflammatory mediators such as NO, iNOS, and COX-2 [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported induction of oxidative stress during fracture healing in animal models [ 33 , 34 , 45 ]. Oxidative stress is involved in ankle fractures in children [ 46 ], in burst spinal fractures [ 47 ], in osteoporotic spinal fractures treated with kyphoplasty [ 48 ], and mandible fractures internally fixed with titanium alloy plates [ 49 ]. Decreased levels of antioxidant defense enzymes in femoral head fracture patients as compared to a healthy population have been reported, and it has been suggested that oxidative stress and anti-inflammatory markers like interleukins might play an important role in bone fracture pathogenesis and in bone density changes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…et al demonstrated that SIN (100 mg/kg) notably reduced body weight and DAI score, ameliorated colon shortening in mice with DSS-induced colitis via activating the Nrf2/NQO-1 pathway [ 105 ]. J. Shen and team found that SIN (0.25–1 mM) mitigated BK-induced inflammation in MG-63 cells by downregulating IL-1β, IL-6, TNF-α, p-p38, and p-NF-κB-p65 in the P38 MAPK and NF-κB signaling pathways, reduced MDA, increased SOD and CAT, and upregulated Nrf2, HO-1, and NQO-1 via the inhibition of Nrf2 pathway activation ( Figure 8 ) [ 106 ]. S.P.…”
Section: Anti-inflammatory Activity and Analgesic Activitymentioning
confidence: 99%
“…↓: NF-κB and MAPK, TNF-α, IL-6, IL-1β, IL-8, COX-2, iNOS, and MMP-2SOD, CAT, Nrf2, HO-1, NQO-1, and Nrf2. ↓: MAPKP38/NF-κB, IL-1β, IL-6, TNF-α, p-p38, p-NF-κB (P65), and MDA.NR[106]…”
mentioning
confidence: 99%